The popular participation in the political-administrative enancy of Tamandaré/PE / A participação popular na emancipação político-administrativa de Tamandaré/PE - Maria do Carmo Ferrão Santos (Universidade Estadual de Alagoas, 2019)
The purpose of this article is to narrate the whole organization process to gain the emancipation of the municipality of Tamandaré, for this purpose, it addresses: - the reasons that stimulated the inhabitants of the districts of Tamandaré and Saué (located on the southern coast of Pernambuco) to fight for independence in relation to Rio Formoso (mother-city); - the campaign for the holding of the plebiscite; - the promulgation of the political-administrative emancipation of the municipality of Tamandaré. For this purpose, information was sought from the TER-PE, Legislative Assembly-PE, Rio Formoso City Hall, and in several events with the constant presence of the author of this work. The results point out that emancipation was a very important historical fact for the freedom of the people who live in it and depends on it to survive.